2013
DOI: 10.1016/j.jpowsour.2013.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi-walled carbon nanotubes on the stability of dye sensitized solar cells

Abstract: h i g h l i g h t s< We studied dye sensitized solar cells with and without addition of carbon nanotubes. < CNTs can improve both photoconversion efficiency and operational stability. t r a c tWe report the improvement of the operational stability of dye-sensitized solar cells (DSSCs) by incorporating multi-wall carbon nanotubes (MWCNTs) in conventional nanostructured semiconducting TiO 2 photoanodes. DSSCs were prepared by adding various concentrations of MWCNTs (up to 1.0% wt.) to TiO 2 anatase nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…CNT-based architectures can be used as a conducting scaffold in a TiO 2 semiconductor based photoelectrochemical cell with the effect of increasing the PCE by a factor of 2 (ref 7) or cell stability. 27 Here, we present a simple, fast, and low-cost fabrication method for the integration of MWCNTs in TiO 2 photoanodes to enhance the functional properties of DSCs. The process is highly reproducible and leads to 25% improvement of PCE with respect to the photoanode without adding CNTs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…CNT-based architectures can be used as a conducting scaffold in a TiO 2 semiconductor based photoelectrochemical cell with the effect of increasing the PCE by a factor of 2 (ref 7) or cell stability. 27 Here, we present a simple, fast, and low-cost fabrication method for the integration of MWCNTs in TiO 2 photoanodes to enhance the functional properties of DSCs. The process is highly reproducible and leads to 25% improvement of PCE with respect to the photoanode without adding CNTs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, several authors have made a similar observation on this optimized value of CNT content and suggested that a concentration range between 0.01 and 0.03 wt% CNTs in TiO 2 fi lms is suitable to achieve high-performance DSSCs. [ 201,213,214 ] It is surprising that this optimized CNT concentration is very different from that (0.1-0.3 wt%) found in some other works.…”
Section: Semiconducting Layers With Cntsmentioning
confidence: 70%
“…Since this signifi cant improvement in the DSSC performance was demonstrated by these authors using CNTs, considerable attention has been paid to the research on this topic. [96][97][98][99][100][101][102][103][104][105][106][107][108][109] For instance, Lin et al [ 99 ] prepared bilayer structured photoelectrode fi lms composed of multi-walled carbon nanotubes (MWCNTs)-TiO 2 /TiO 2 which when used in DSSCs exhibited two times higher PV effi ciency than the cell fabricated with the bare TiO 2 fi lm. This improvement in the PV performance has been demonstrated to be related to the 1D CNT which supports transfer of the photo-generated charges quickly, thus suppressing charge recombination.…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…In order to obtain a balance between the R ct and IPCE, several efforts have been undertaken with different concentrations of CNTs structures. [ 97,[100][101][102][103][104] In these studies, the optimized concentrations of CNTs in TiO 2 fi lms were relatively different because the corresponding DSSCs were fabricated under different experimental conditions. A general method to prepare CNTs/TiO 2 photoelectrodes is as follows: CNTs are fi rst chemically treated using acid solutions (HNO 3 or H 2 SO 4 ) to generate functional groups such as hydroxyl (-OH), carbonyl (C=O) and carboxyl (-COOH) groups.…”
Section: Reviewmentioning
confidence: 99%